Analysis of The Causes of Crankshaft Failure In The Komatsu Egs 1200 Diesel Engine at Pt. Pltd Bengkalis - Hardi; Ibnu Hajar (International Journal of Science and Environment (IJSE), 2026)
This study was conducted to analyze the causes of crankshaft failure in the Komatsu EGS 1200 diesel engine at PT. PLTD Bengkalis. The crankshaft is one of the most critical components of a diesel engine, functioning to convert the reciprocating motion of the piston into rotational motion. Failure of the crankshaft can disrupt engine operation and result in significant downtime at the power generation plant. This study aims to identify the primary factors causing crankshaft failure and to propose corrective actions to minimize future failures.The research employed the Failure Mode and Effects Analysis (FMEA) method. The research data were collected through direct observation, documentation, interviews, and operational data obtained from the Komatsu EGS 1200 diesel engine at PT. PLTD Bengkalis. The analysis was carried out by identifying potential failure modes, their causes, and the effects of these failures on the diesel engine system.The results indicate that crankshaft failure is influenced by several factors, including inadequate lubrication, excessive operating loads, material fatigue, overheating, and misalignment of engine components. Based on the FMEA analysis, the most critical factors contributing to crankshaft damage were identified, providing a basis for developing effective maintenance strategies and preventive measures to reduce future failures. This study is expected to improve the reliability of diesel engines and minimize the risk of failures in power generation systems.